Acreditación en la Facultad de Ingeniería Industrial de la Universidad Nacional Mayor de San Marcos - Factor analizado: Procesos Académicos - Rojas Lazo, Oswaldo (2011)
The present upgrading work pretends to be a document that allows the delivering of experiences got by the Industrial Engineering Faculty (FII by its acronyms in Spanish) of the National University of San Marcos (UNMSM by its acronyms in Spanish), to obtain the university accreditation. The factor denominated Academic Processes is analyzed specifically, framed as part of the development of the teaching - learning process under the principle of continuous improvement that finally had the effect to be the first school of Industrial Engineering in Peru in being internationally accredited.